Polymer-Bioactive Glass Composite Filaments for 3D Scaffold Manufacturing by Fused Deposition Modeling: Fabrication and Characterization - Distler, Thomas; Fournier, Niklas; Grünewald, Alina; Polley, Christian; Seitz, Hermann; Detsch, Rainer; Boccaccini, Aldo R. (Frontiers in Bioengineering and Biotechnology, 2020)
The treatment of critical size bone defects, for example resulting from large tumor resections, still remains a challenge in clinical practice. It has been demonstrated that the gold standard treatment based on auto- and allografts can provide aid in some cases. However, the development of patient specific 3D printed implants and modern biomaterial-based bone tissue engineering (TE) strategies, avoiding the requirement of harvesting bone in a donor site, promises to be the next generation treatment for bone healing. We present a PLA-Bioactive glass (BG) scaffold manufacturing technology based on fused deposition modelling (FDM), involving the fabrication of PLA-BG composite filaments which are used to 3D print controlled open-porous and osteoinductive scaffolds. We confirm the printability, bioactivity and biocompatibility of the scaffolds using pre-osteoblast MC-3T3 E1 cells. Gene expression analyses revealed the beneficial impact of BG inclusions in FDM scaffolds regarding osteoinduction, leading to an increased osteogenic differentiation of adipose derived stem cells in comparison to pristine PLA. FDM is confirmed as a suitable additive manufacturing method to develop PLA-BG composite scaffolds suitable to bone tissue engineering.